Generation of reactive oxygen species by mitochondria - Cadenas, Enrique; Han, Derick (Henry Stewart Talks, 2007)
Oxygen chemistry, Reactive oxygen species chemistry and in disease, Antioxidants defenses, Mitochondria structure and topology, Mitochondria bioenergetics, Sites and mechanisms, Superoxide dismutase, Mitochondrial GSH, Superoxide generation, Voltage-dependent anion channels, Methods to measure reactive oxygen species, Regulation of mitochondrial reactive oxygen species generation, Rate of respiration by the electron transport chain, Ceramide, Nitric oxide, Post-translational modification
Archived at 2018/05/31